Connected soldiers : life, leadership, and social connections in modern war - Spencer, John, 1975- (Potomac Books, an imprint of the University of Nebraska Press, 2022)
"Connected Soldiers recounts the action sequences that made the author a great combat leader, the methods he used to build unit cohesion, and then how he supported his wife as a stay at home father when his wife went off to war"--